Molecular Products and Fundamentally Based Reaction Pathways in the Gas-Phase Pyrolysis of the Lignin Model Compound p-Coumaryl Alcohol - Asatryan, Rubik (J Phys Chem A, 2017)
The fractional pyrolysis of lignin model compound para-coumaryl alcohol (p-CMA) containing a propanoid side chain and a phenolic OH group was studied using the System for Thermal Diagnostic Studies at temperatures from 200 to 900 °C, in order to gain mechanistic insight into the role of large substituents in high-lignin feedstocks pyrolysis. Phenol and its simple derivatives p-cresol, ethyl-, propenyl-, and propyl-phenols were found to be the major products predominantly formed at low pyrolysis temperatures (<500 °C). A cryogenic trapping technique was employed combined with EPR spectroscopy to identify the open-shell intermediates registered at pyrolysis temperatures above 500 °C. These were characterized as radical mixtures primarily consisting of oxygen-linked conjugated radicals. A comprehensive potential energy surface analysis of p-CMA and p-CMA + H atom systems was performed using various DFT protocols to examine the possible role of concerted molecular eliminations and free-radical mechanisms in the formation of major products. Other significant unimolecular concerted reactions along with formation and decomposition of primary radicals are also described and evaluated. The calculations suggest that a set of the chemically activated secondary radical channels is relevant to the low temperature product formation under fractional pyrolysis conditions.